Measurement Time in the Evaluation of Whole-Body Vibration: The Case of Mechanized Wood Extraction with Grapple Skidder - Lima, Roldão Carlos Andrade [UNESP]; Minette, Luciano José; Simões, Danilo [UNESP]; Rocha, Qüinny Soares [UNESP]; Miyajima, Ricardo Hideaki [UNESP]; Fritz, Gabriel Fratta [UNESP]; Schettino, Stanley; Soranso, Denise Ransolin; Nascimento, Glícia Silvania Pedroso; Vieira, Marlice Paes Leme; Schettini, Bruno Leão Said; Silva, Arthur Araújo (MDPI, 2023)
The grapple skidder is a self-propelled forestry machine that is used for the extraction of trees in wood harvesting—commonly used in full tree systems. Moving this machine can expose operators to occupational hazards of physical origin, among which whole body vibration stands out. However, the measurement of this risk agent does not have a standard measurement time, being performed for periods of approximately 30 min—disregarding the time of the daily workday. In view of this, it was analyzed whether occupational exposure to whole body vibration transmitted to grapple skidder operators using different measurement times complies with the guidelines for preventative purposes. Thus, measurements of whole-body vibration were carried out along three orthogonal axes over a period of one hour and over a daily workday of eight hours—by which were measured the daily (8 h) vibration exposure for the l-axis and the vibration value. The acceleration values in the three evaluated axes were higher for the daily working day, denoting the influence of the measurement time. In addition, the vibration dose value resulted in values above the action limit for both evaluations; however, the daily workload was highlighted—indicating the presence of higher vibration peaks over a longer measurement time. Thus, the assertiveness and influence of measurement times over the daily working day for whole-body vibration transmitted to grapple skidder operators is evidenced.
Keywords: forestry operations; occupational health; occupational vibration; wood harvesting